2020
DOI: 10.1093/mnras/staa091
|View full text |Cite
|
Sign up to set email alerts
|

The WAGGS project-III. Discrepant mass-to-light ratios of Galactic globular clusters at high metallicity

Abstract: Observed mass-to-light ratios (M/L) of metal-rich globular clusters (GCs) disagree with theoretical predictions. This discrepancy is of fundamental importance since stellar population models provide the stellar masses that underpin most of extragalactic astronomy, near and far. We have derived radial velocities for 1,622 stars located in the centres of 59 Milky Way GCs -twelve of which have no previous kinematic information -using integral-field unit data from the WAGGS project. Using N-body models, we determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Integral field spectroscopy (e.g. Lanzoni et al 2013;Kamann et al 2014;Dalgleish et al 2020) allows spectra to be observed even in dense fields, especially when used with techniques to reliably extract spectra from blended stars (Kamann, Wisotzki & Roth 2013). With wide field integral field spectrographs, large numbers of spectra can be obtained at once, with Kamann et al (2018a) measuring the radial velocities of over 200 000 stars in 22 GCs using MUSE (the Multi-Unit Spectroscopic E-mail: chris.usher@astro.su.se Explorer, Bacon et al 2010) on the European Southern Observatory Very Large Telescope (VLT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integral field spectroscopy (e.g. Lanzoni et al 2013;Kamann et al 2014;Dalgleish et al 2020) allows spectra to be observed even in dense fields, especially when used with techniques to reliably extract spectra from blended stars (Kamann, Wisotzki & Roth 2013). With wide field integral field spectrographs, large numbers of spectra can be obtained at once, with Kamann et al (2018a) measuring the radial velocities of over 200 000 stars in 22 GCs using MUSE (the Multi-Unit Spectroscopic E-mail: chris.usher@astro.su.se Explorer, Bacon et al 2010) on the European Southern Observatory Very Large Telescope (VLT).…”
Section: Introductionmentioning
confidence: 99%
“…Dotter et al 2010;VandenBerg et al 2013), metal-poor ([Fe/H] =−2.33, Carretta et al 2009) GC with a mass of ∼ 5 × 10 5 M (e.g. Dalgleish et al 2020). According to the 2010 edition of the Harris (1996) catalogue, M15 lies 10.4 kpc from the Sun as well as 10.4 kpc from the Galactic centre.…”
Section: Introductionmentioning
confidence: 99%
“…Since the observed 𝑀/𝐿 𝑉 of the clusters in our sample are smaller than SSP model predictions, the argument above implies that a bottom light IMF is needed to reconcile the data and models in the absence of any other effects-such as dynamical evolution as discussed above-which may alter 𝑀/𝐿 𝑉 . We follow the discussion of Dalgleish et al (2020) who defined two simple power-law mass functions (MF). In both cases, 𝛼 3 = 2.3 (the same as the Kroupa IMF), but for lower stellar masses between 0.08 and 1.0 M , 𝛼 1 = 𝛼 2 = 1.3 for their so-called 'bottom-light' MF, and 𝛼 1 = 𝛼 2 = 0.3 for their 'extreme bottom-light' MF.…”
Section: Variations In the Stellar Initial Mass Function?mentioning
confidence: 99%
“…Some of these studies have revealed variations of 𝑀/𝐿 ratios with respect to metallicity and cluster masses that do not appear to conform to model expectations (e.g. Strader et al 2009Strader et al , 2011Kimmig et al 2015;Baumgardt 2017;Dalgleish et al 2020).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation